Analisis Kritis Kesalahan Ejaan dan Tanda Baca dalam Novel Laut Bercerita Karya Leila S. Chudori - Anisa Maulidiya Istikomah; Dista Dwi Maharani; Dea Suryaningtyas; Mohamad Afrizal (Universitas Sultan Ageng Tirtayasa, 2026)
This study analyzes language editing in the novel Laut Bercerita by Leila S. Chudori, focusing on spelling and punctuation errors based on the Indonesian Spelling Guidelines (PUEBI). Using a descriptive qualitative method, the study examines forms of errors, underlying linguistic factors, and their categorization. Data were collected through intensive reading of the novel and documentation of linguistic inaccuracies. The data were then analyzed using PUEBI and the Kamus Besar Bahasa Indonesia (KBBI). The findings reveal errors related to capitalization, nonstandard words, foreign-term writing, and punctuation use. These deviations are influenced by spoken-language interference, stylistic choices, and aesthetic considerations. Some deviations also function as literary devices that enhance characterization, emotional expression, and narrative atmosphere. The study emphasizes the importance of contextual language editing in literary works by balancing linguistic accuracy with artistic expression.